Sosialisasi Peran Tanaman Obat Keluarga (Toga) dalam Mengembangkan Kesehatan Masyarakat Desa Bancer - Azhar, Sarah Ardina Al; Farahdiansari, Ardana Putri; Damayanti, Chusnul Chotimah; Putri, Aida Dinda (Unri Conference Series: Community Engagement, 2024)
TOGA plant is a family medicinal plant that has many properties that can be processed into traditional herbal medicine to overcome various health problems. TOGA plants do not need a large land, just by utilizing an empty yard to be useful. The lack of knowledge and awareness of the people of Bancer Village, Ngraho District, Bojonegoro Regency about the efficacy of the TOGA plant is a problem. KKN-TK students of group 19 of Bojonegoro University conducted counseling and socialization directly by involving housewives in Bancer Village with the aim of recalling the benefits of TOGA plants for health, in addition to practical training and direct guidance on planting TOGA plants in the yard to be used and cultivated. The method of implementing this activity includes observation, socialization, as well as practice and community empowerment by involving the people of Bancer Village. This activity succeeded in increasing residents' awareness of the importance of utilizing vacant land to plant crops that are beneficial to family health and also the practice of planting TOGA at the houses of the heads of RT.03 and RW.04. Considering the enthusiasm of the people of Bancer Village, the community can be more productive by using the yard to plant TOGA plants that can be used to meet the needs of herbal medicines independently and of course improve the health of the people of Bancer Village, Ngraho District.